Efektivitas Pengaruh Media Pembelajaran Berteknologi Terhadap Pencapaian Belajar Matematika di Masa Industri 5.0 - Khisan, Hindun Asvi Khaerotul; Subekti, Fitrianto Eko (UM Purwokerto Press, 2025)
Mathematics, as a core subject, continually evolves to align with societal demands and technological advancements. Despite its essential role, challenges persist in mathematics education, particularly concerning students’ low interest and suboptimal academic achievement. Reports from UNESCO and international assessments such as PISA indicate that Indonesian students consistently perform poorly in mathematics. One contributing factor is the less effective utilization of instructional media by educators. Card-based learning tools have been identified as an effective strategy to boost students’ motivation and understanding of mathematical concepts. This study employs a Systematic Literature Review (SLR) approach to comprehensively examine the application of card media in mathematics instruction. A total of eight relevant studies were selected using specific inclusion and exclusion criteria. The findings indicate that card-based media, especially at the primary education level, significantly enhances students’ learning outcomes across various educational stages. Most of the analyzed research adopted the classroom action research model by Kemmis and McTaggart. The most frequently addressed topic was number concepts. On average, learning outcomes improved by 14.69% through the implementation of card media. These results suggest that card-based instructional media is a promising pedagogical tool that should be more widely adopted in mathematics classrooms.